Predictors of PTSD symptoms in brazilian police officers: the synergy of negative affect and peritraumatic dissociation Preditores de sintomas de transtorno de estresse pós-traumático em policiais brasileiros: a interação entre afeto negativo e dissociação peritraumática - Deborah B Maia (Brazilian Journal of Psychiatry, 2011)
BACKGROUND: Exposure to traumatic events is a necessary but not a sufficient condition for the development of posttraumatic stress disorder (PTSD). Pretrauma, peritrauma and posttrauma factors interact to impact on symptom severity. The aim of the present study is to determine risk factors for PTSD symptoms in Brazilian police officers. METHOD: In a cross-sectional sample of active duty officers (n = 212), participants were asked to complete a socio-demographic questionnaire and self-report scales on affective traits, cumulative critical incident exposure, peritraumatic distress and dissociation, PTSD symptoms, and social support. Hierarchical linear regression analysis was conducted to examine predictors of PTSD symptoms. RESULTS: Variables related to negative affect, job duration, frequency of critical incident exposure, peritraumatic dissociation, and lack of social support remained significant in the final model and explained 55% of the variance in PTSD symptoms. When interaction terms were evaluated, a synergistic effect between negative affect and peritraumatic dissociation was found. CONCLUSIONS: The risk factors found in this study provide clues on how to elaborate primary prevention strategies regarding PTSD symptoms in police officers. Such initiatives may lessen the impact of repeated exposure to traumatic events on police officers over the course of their careers. INTRODUÇÃO: A exposição a eventos traumáticos é uma condição necessária, porém não única, para o desenvolvimento de transtorno de estresse pós-traumático (TEPT). Fatores individuais pré, peri e pós-trauma exercem impacto sobre a gravidade dos sintomas. O objetivo do presente estudo é determinar os fatores de risco para o desenvolvimento de sintomas de TEPT em policiais brasileiros. MÉTODO: Uma amostra transversal de policiais em atividade (n = 212) foi convidada a responder um questionário sóciodemográfico e escalas autoaplicáveis sobre afeto positivo e negativo, frequência de incidentes críticos, sofrimento e dissociação peritraumáticos, sintomas de TEPT e apoio social. Regressão linear hierárquica foi utilizada para avaliar fatores de risco. RESULTADOS: Afeto negativo, tempo de trabalho, frequência de exposição a eventos traumáticos, dissociação peritraumática e apoio social diminuído permaneceram no modelo final e explicaram 55% das variações dos sintomas de TEPT. Foi observado efeito sinérgico entre dissociação peritraumática e afeto negativo. CONCLUSÃO: Baseados nos achados os autores discutem estratégias de prevenção que visam diminuir o impacto da exposição a eventos traumáticos em policiais ao longo de suas carreiras.